Persepsi dan Partisipasi Masyarakat dalam Pengembangan Kawasan Wisata Air Terjun Ogi Di Kelurahan Faobata, Kecamatan Bajawa, Kabupaten Ngada - Deru, Selfia; Leha, Ernesta; Penu, Yustina Paulina (JURNAL EQUILIBRIUM, 2022)
This study aims to find out how the Perception and Participation of the Community in the Development of the Ogi Waterfall Tourism Area in Faobata Village, Bajawa District, Ngada Recency by using a qualitative descriptive analysis tool. To obtan data used data collection techniques in the form of observation, questionnaires, and documentation. The sample in this study were 100 people. The results of the study show that the existence of the Ogi Waterfall tourist area has a positive impact on the community. In this case it can incrlhbbn ease onomic and opening new job for people who are unemployed.